Cerebrovascular Reactivity Is a Main Determinant of White Matter Hyperintensity Progression in CADASIL - Liem, M.K.; Lesnik Oberstein, S.A.J.; Haan, J.; Boom, R.v.d.; Ferrari, M.D.; Buchem, M.A.v.; Grond, J.v.d. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Basal total cerebral blood flow (TCBF) and cerebrovascular reactivity (CVR) are assumed to play an important role in the pathophysiology of small-vessel disease. Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a unique monogenetic model to study the pathophysiology of arterial small-vessel disease. The aim of this study was to investigate the role of TCBF and CVR in the progression of MR imaging abnormalities in CADASIL.MATERIALS AND METHODS: Basal TCBF was measured in 25 NOTCH3 mutation carriers and 13 control subjects at baseline. CVR after administration of acetazolamide was measured in 14 NOTCH3 mutation carriers and 9 control subjects. Increase in white matter hyperintensities (WMHs), lacunar infarcts, and microbleeds on MR imaging was measured 7 years later.RESULTS: Lower CVR at baseline was associated with larger increase of WMHs (P = .001) but not with a larger increase of lacunar infarcts or microbleeds. TCBF at baseline was not associated with an increase of MR imaging abnormalities.CONCLUSIONS: Decreased CVR is a potential predictor of disease progression as indicated by increasing WMHs in CADASIL.